The centennial collection [compact disc] - Johnson, Robert, 1911-1938 (Columbia/Legacy, 2011)
May 8, 2011, marks the 100th birthday of Mississippi Delta bluesman Robert Johnson, who, according to legend, sold his soul down at the crossroads of Highway 61 and Highway 49 in a midnight bargain that has haunted the music world for three-quarters of a century. The deal brought forth Johnson s incandescent guitar technique and a run of 10-inch 78 rpm singles for the Vocalion, Oriole, Conqueror and Perfect labels recorded in San Antonio in 1936 and Dallas in 1937. Those songs have become a cornerstone of Columbia Records identity and will be celebrated on The Centennial Collection. This 2CD set shares the same genealogy as 1990 s Robert Johnson -The Complete Recordings, but that package has now been updated for a new generation. The set includes a new essay by Ted Gioia alongside a new biography of Robert Johnson written by Stephen C. LaVere (completely different from his essay in the 1990 version). Also included are new illustrations, photo images, and a family tree of music originating from Robert Johnson.